J-PAS: forecasts on interacting vacuum energy models. Issue 9 (23rd September 2021) - Salzano, V.; Pigozzo, C.; Benetti, M.; Borges, H.A.; von Marttens, R.; Carneiro, S.; Alcaniz, J.S.; Fabris, J.C.; Tsujikawa, S.; Benítez, N.; Bonoli, S.; Cenarro, A.J.; et al.
Abstract: The next generation of galaxy surveys will allow us to test some fundamental aspects of the standard cosmological model, including the assumption of a minimal coupling between the components of the dark sector. In this paper, we present the Javalambre Physics of the Accelerated Universe Astrophysical Survey (J-PAS) forecasts on a class of unified models where cold dark matter interacts with a vacuum energy, considering future observations of baryon acoustic oscillations, redshift-space distortions, and the matter power spectrum. After providing a general framework to study the background and linear perturbations, we focus on a concrete interacting model without momentum exchange by taking into account the contribution of baryons. We compare the J-PAS results with those expected for DESI and Euclid surveys and show that J-PAS is competitive to them, especially at low redshifts. Indeed, the predicted errors for the interaction parameter, which measures the departure from a ΛCDM model, can be comparable to the actual errors derived from the current data of cosmic microwave background temperature anisotropies.